Heat stress exacerbates the reduction in middle cerebral artery blood velocity during prolonged self-paced exercise - Periard, J. D.; Racinais, S. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study examined the influence of hyperthermia on middle cerebral artery mean blood velocity (MCA Vmean). Eleven cyclists undertook a 750?kJ self-paced time trial in HOT (35 °C) and COOL (20 °C) conditions. Exercise time was longer in HOT (56 min) compared with COOL (49 min; P < 0.001). Power output in HOT was significantly lower from 40% of work completed onward (P < 0.01). Rectal temperature increased to 39.6 ± .6 C (HOT) and 38.8 ± 0.5 °C (COOL; P < 0.01). Skin temperature, skin blood flow, and heart rate were higher throughout HOT compared with COOL (P < 0.05). A similar increase in ventilation (P < 0.05) and decrease in end-tidal partial pressure of CO2 (PETCO2; P < 0.05) occurred in both conditions. Arterial blood pressure and oxygen uptake were lower from 50% of work completed onward in HOT compared with COOL (P < 0.01). MCA Vmean increased at 10% in both conditions (P < 0.01), decreasing thereafter (P < 0.01) and to a greater extent in HOT from 40% of work completed onward (P < 0.05). Therefore, despite a comparable ventilatory response and PETCO2 in the HOT and COOL conditions, the greater level of thermal strain developing in the heat appears to have exacerbated the reduction in MCA Vmean, in part via increases in peripheral blood flow and a decrease in arterial blood pressure.